Pengaruh Pembinaan Dinas Sosial terhadap Kemampuan Kognitif dan Afektif Siswa Putus Sekolah pada Jenjang Pendidikan Dasar - Ardalina, Ardalina; Witarsa, Ramdhan; Daulay, Musnar Indra (Universitas Negeri Makassar, 2024)
Social Service coaching is one of the ways used by the Social Service to control dropout students to return to school. This research aims to measure how much influence the Social Service coaching has on the cognitive and affective abilities of dropout students at the primary education level. The method used in this research is the quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting the research problem, developing research hypotheses, creating a research design, conducting pretests, conducting experiments, conducting post-tests, processing and analysing data, and drawing conclusions. The research sample totalled 30 students, consisting of 15 students in the experimental class and 15 students in the control class. The data collection techniques used were cognitive and affective tests. The results showed that the application of Social Service coaching had a significant effect on the cognitive and affective abilities of dropout students. Coaching dropout students must continue to be carried out so that they want to return to school and achieve their goals.